The correlation between the intensity of prenatal yoga participation on anxiety levels for third trimester pregnant women in facing childbirth in Kartasura district - Maharani, Hervina Wilhelmina; Nurhidayati, Siti; Argaheni, Niken Bayu; Maulida, Luluk Fajria; Sukamto, Ika Sumiyarsi (Journal of Health Technology Assessment in Midwifery, 2022)
Background:Data from the World Health Organization (WHO) show that pregnant women experience anxiety by 8-10% during pregnancy, and it increases to 13% when they are about to give birth. The incidence of anxiety in pregnant women in Indonesia reaches 373,000, 28.7% of which anxiety occurs in pregnant women when facing childbirth. Sustained anxiety will increase the likelihood of cesarean section, prolonged second stage, asphyxia and affect fetal neurodevelopment and fetal cognitive. One of the physical exercises that can reduce anxiety is prenatal yoga. The purpose of this study was to determine the relationship between the intensity of prenatal yoga participation on the level of anxiety of pregnant women in the third trimester in facing childbirth in Kartasura District.Methods: Cross-sectional study design. The population in this study were all third trimester pregnant women who did prenatal yoga and did prenatal checkups at midwife Wulan, Anik Midwife Health House and Auliya Husada Clinic with a total population of 42 people. The sample of this study used accidental sampling and total sampling. The research instrument used the Perinatal Anxiety Screening Scale (PASS), and used univariate and bivariate data analysis with the Spearman test.Results: A total of 22 pregnant women who did not participate in prenatal yoga experienced severe anxiety by 54.6% (12 people), while of the 20 pregnant women who participated in prenatal yoga, most experienced mild anxiety by 50% (10 people). Based on statistical tests using the Spearman test, p-value <0.05 was obtained.Conclusion: There is a relationship between the intensity of prenatal yoga participation on the level of anxiety of pregnant women in the third trimester in facing childbirth in Kartasura District.Suggestion: It is hoped that pregnant women who have not followed prenatal yoga regularly participate in prenatal yoga in order to reduce discomfort and anxiety.